Going beyond the hype: conceptualising "media ecosystem" for media management research. Issue 1 (2nd January 2021) - Kostovska, Ivana; Raats, Tim; Donders, Karen; Ballon, Pieter
ABSTRACT: Faced with competition from electronic communications, ICT and social media firms, and confronted with multi-sided platforms occupying numerous gatekeeping positions, media firms have to rely on others to create value. Competing means collaborating and supporting others to innovate and create joint value. Taking these changes into account, the use of "ecosystem", in addition to allied concepts such as platform, became more prominent. Ecosystems allow actors to create value that none of them is able to do on their own. This article explains why the concept of media ecosystem can be useful in media management research and in practice and defines and operationalises the concept in a model that can be used for empirical research and in practice.